Effects of the initial droplet temperature on the vaporization process at high pressure - Fachini,Fernando F. (2007)
The aim of this study is to determine conditions for the quasi-steady regime (QSR) of vaporization of Methanol droplets in high pressure Nitrogen. Under the quasi-steady regime, the square of the droplet radius decreases linearly with time (QSR), a simple result that can be easily implemented in numerical codes. Nevertheless, the vaporization rate cannot be described by a simple expression. The vaporization rate depends initially on the quantity of gas dissolved inside the droplet, on the liquid phase expansion and on the mass loss to the gas phase which is controlled by the initial conditions of the droplet. After this initial period and the droplet heating period, when the heat flux from the gas phase is almost completely employed to vaporize the droplet, the vaporization rate can be expressed approximately by a quasi-steady model. As shown by the numerical results, the main unsteadiness source for the droplet vaporization at high pressure is the droplet heating.